Effect of submucosal injection in endoscopic papillectomy of ampullary tumor: Propensity-score matching analysis. Issue 4 (May 2018) - Chung, Kwang Hyun; Lee, Sang Hyub; Choi, Jin Ho; Kang, Jinwoo; Paik, Woo Hyun; Ahn, Dong-Won; Ryu, Ji Kon; Kim, Yong-Tae
Background: The role of submucosal injection (SI) in endoscopic papillectomy (EP) is controversial. Objective: This study investigated the effects of SI before EP of ampullary tumors. Methods: All patients who underwent initial curative EP at our institution between March 2006 and March 2014 were retrospectively recruited. The presence of residual tumor after three months, recurrence-free survival and post-procedural adverse events were compared between the SI group and non-injection (NI) group. Propensity-score matching was performed between the two groups to reduce potential selection bias and confounding. Results: A total of 122 patients were included (SI: 26, NI: 96). Following propensity-score matching, 25 paired patients were selected. Residual tumor was not shown in the NI group, whereas seven (28.0%) patients in the SI group had residual tumor ( p  = 0.010). The recurrence-free survival of the NI group was significantly longer than that of the SI group ( p  = 0.036). Upon multivariate analysis, pathologic grade ( p  = 0.026) and SI ( p  = 0.033) were significantly related to recurrence-free survival. Post-procedural adverse events were not significantly different between the two groups. Conclusion: SI before EP of ampullary tumor was related to more frequent residual tumor and shorter recurrence-free survival and did not reduce post-procedural adverse events.